A History of Endometriosis Is Associated With Decreased Peripheral NK Cytotoxicity and Increased Infiltration of Uterine CD68+ Macrophages - Wang, Linlin; Li, Longfei; Li, Yuye; Huang, Chunyu; Lian, Ruochun; Wu, Tonghua; Ma, Jingwen; Zhang, Yan; Cheng, Yanxiang; Diao, Lianghui; Zeng, Yong (Frontiers in Immunology, 2021)
Women with endometriosis may have a defective immune system. However, evidence of the immune responses of endometriosis patients with a history of endometriosis surgery is lacking, and the association between the location of endometriosis lesions and immune responses is unclear. This retrospective study included 117 females with reproductive failure and a history of endometriosis and 200 females with reproductive failure but without endometriosis to analyze their endometrial and peripheral immune responses. The results show that endometriosis was associated with decreased peripheral natural killer (NK) cytotoxicity and increased uterine macrophages. Peripheral NK cytotoxicity at effector-to-target ratios of 25:1 and 50:1 was significantly reduced in women with a history of endometriosis from that of the control group (26.6% versus 33.3% and 36.1% versus 43.3%, respectively, both P < 0.001). Furthermore, after further division of patients into three subgroups according to the location of endometriosis lesions, we observed that NK cytotoxicity in the endometriosis subgroups, especially the mixed endometriosis group, was strongly decreased from that of the controls (P = 0.001). The endometrial CD68+ macrophage proportion in the mixed endometriosis subgroup was higher than that in the control group (2.8% versus 2.1%, P = 0.043). In addition, the baseline estradiol (E2) level was weakly correlated with the percentage of endometrial macrophages (r = 0.251, P = 0.009), indicating a potential association among the endocrine system, endometrial immune environment, and endometriosis. This study indicated that peripheral NK cytotoxicity and endometrial immune cell profiles could be useful for diagnosing and treating endometriosis and endometriosis-related reproductive diseases.